Education for Ethnic-Racial Relations: conceptions and practices of Early Childhood Education teachers (Research, Society and Development, 2021)
This research presents the results of a Course Completion Work produced in the Pedagogy Degree at the Federal University of Pampa - Campus Jaguarão / RS. The objective was to understand which conceptions and practices the teachers of a school of Early Childhood education in the city of Arroio Grande / RS, have of Education for Ethnic-Racial Relations having as guidance the Law 10.639 / 2003. The motivation for the elaboration of this research was based on the reflection of the practice of the Supervised Internship and by understanding that this is the fundamental moment for the academic to correlate theory and practice. Methodologically, it presents a qualitative nature and is procedurally classified as a case study. The fieldwork was carried out during the months of September and October of the year 2019, with empirical data obtained from a semi-structured interview, applied to eight teachers from the municipal network. The participants had between one and 15 years of teaching work. The information was analyzed and interpreted in the light of the historical-critical perspective, based on the Content Analysis methodological basis. Results indicated the theoretical-conceptual weakness of the subjects in relation to the approach to Education for Ethnic-Racial Relations in Early Childhood Education, signaling the need for the implementation of more effective continuous training and the insertion of specific curricular components in teacher training courses. To this end, this study was based on the theoretical formulations of Bardin (2016), Caldeira (2010), Rocha (2007), Silva (2018), Cavalleiro (2017), Gomes (2015), Malheiro (2005), Veiga (2013), among others.